Analisis Pemberian Hadiah Pada Produk Simjakasya Berhadiah Di Awal Berdasarkan Fatwa DSN-MUI Nomor 86/DSN-MUI/XII/2012 Tentang Hadiah Dalam Penghimpunan Dana Lembaga Keuangan Syariah Di BMT NU Ngasem Jawa Timur - Muhammad Agus Arya Sukma; Rudi Hermawan (Pusat Riset dan Inovasi Nasional, 2023)
A gift is a present made voluntarily by someone to another person without compensation or expecting anything in return except to get closer to Allah SWT, which results in the transfer of ownership from the giver to the person given. Giving gifts is a natural thing in deposits in Islamic financial institutions that use the wadi>`ah yad dama>nah contract. Therefore, this study analyzes the giving of prizes to Simjakasya products with prizes at the beginning based on the DSN-MUI Fatwa Number 86/DSN-MUI/XII/2012 concerning Prizes in Fundraising for Islamic Financial Institutions at BMT NU Ngasem, East Java. This research is a type of field research using qualitative methods. The data sources used are ptimer data sources and secondary data sources. Methods of data collection by way of observation, interviews, and documentation. The research location is at BMT NU Ngasem, East Java. The results of this study indicate that the concept of giving gifts in Simjakasya products with early prizes at BMT NU Ngasem, East Java, there are several things that conflict with the DSN-MUI Fatwa Number 86/DSN-MUI/XII/2012 concerning Prizes in Fundraising for Islamic Financial Institutions. These things are the types of gifts that have been determined and promised beforehand, as well as the custom of BMT to use this concept in every transaction which is a form of custom.